How Non-Native Writers Realize Their Interpersonal Meaning? - Arifin, Adip (Bina Nusantara University, 2018)
This research was aimed at describing and explaining the interpersonal meaning, types of mood system, and modality found in the thesis abstracts. The method used was descriptive qualitative and specifically designed as discourse analysis. The data were taken from two abstracts, written by undergraduate students, majoring in English Language Education atdifferent colleges in Ponorogo, East Java. They were non-native of English. Units of analysis were clauses, words, and phrases. The data were analyzed by using interpersonal meaning theory, proposed by Halliday. The result of this research reveals that firstly, the interpersonal meaning of the abstracts is realized through wordings of the clauses based on the mood system (subject and finite), while the residue is realized through the element of predicator, complement, and adjunct. Secondly, the mood types found are mostly declarative, and only a few of them are interrogative. The declarative form is characterized by order of subject followed by finite, while the interrogative form is characterized by the use of question word, instead of the order of finite and subject. Thirdly, in terms of modality, the abstracts dominantly display the use of low degree modality (can, could, may) which signals the writer’s intention to weaken the authority toward the readers.